A multiple myeloma that progressed as type I cryoglobulinemia with skin ulcers and foot necrosis: A case report. Issue 39 (September 2018) - Solimando, Antonio G.; Sportelli, Azzurra; Troiano, Teresa; Demarinis, Lucia; Di Serio, Francesca; Ostuni, Angelo; Dammacco, Franco; Vacca, Angelo; Ria, Roberto
Abstract: Rationale: Type I cryoglobulinemia is a rare and life-threatening condition. It occurs mainly in B-cell lymphoproliferative disorder. In almost half of the patients, type I cryoglobulinemia is characterized by severe cutaneous involvement. Patient concerns: A 71-year-old man comes to our observation because of the onset of persistence of paresthesia and painful acrocyanosis in the fingers and toes. IgG-k multiple myeloma treated with chemotherapy and radiation therapy on the left iliac wing characterized his clinical history. At the evaluation of response after the first-line therapy, the patient achieved a very good partial response. At the time of progression, the same myelomatous disease has taken a typical behavior of cryoglobulinemia. Diagnoses: Type I multiple myeloma-associated cryoglobulinemia was diagnosed. Interventions: The patient underwent to an immediate composite therapeutic approach based on prostanoid infusion, plasmapheresis along with second-line chemotherapy. Outcomes: Despite the rapid biochemical response, the ischemia of the feet worsened. Moreover, a bacterial infection overlapped. The surgical amputation of both feet was necessary. Allowing MM cytoreduction continuation the patient's clinical condition became stabilized. Lessons: Though rare, type I cryoglobulinemia can be associated with plasma cell dyscrasias. Any delay in diagnosis and the start of therapy can cause worsening of organ damage and endanger the patient's life. Therapeutic strategies in these cases should be directed to the underlying diseases.